The nutcracker - Helbrough, Emma; Luraschi, Anna (Usborne Pub Ltd UK, 2007)
On Christmas Eve, Clara's godfather gives her a present that she stays up until midnight to open, discovering a nutcracker which turns into a prince and herself in need of his protection.